Speaking security: constructing Canada's 2009 northern strategy. Issue 2 (3rd July 2022) - Dean, Ryan
ABSTRACT: The 2006–15 Stephen Harper Conservative government created a Canadian Arctic policy noted as an outlier both at home and abroad. Critics at home alleged that it was a retraction from Canada's overall broadening and deepening Arctic policy trajectory, returning to the narrow concerns of sovereignty. Abroad, the security rhetoric the policy was clad in seemed out of step with the then increasing regional governance of a relatively peaceful Arctic. This article tests these criticisms through a discourse analysis that traces the creation of what is Canada's first integrated Arctic policy during the life of the Harper Conservative government. It applies the Copenhagen School's sectors of security and securitisation theory to mark the breadth and intensity of the discourse over time. It finds that the substance of the policy very much builds upon the preceding work of the Chrétien/Martin government. Whilst the security rhetoric quickly diminished, the actual threats posited conversely built over time with Russia's initial invasion of Ukraine in 2014. It concludes that whilst securitising language often benefits opposition parties, it does not always benefit governments.